"Macho" Beliefs Moderate the Association Between Negative Sexual Episodes and Activation of Incompetence Schemas in Sexual Context, in Gay and Heterosexual Men. Issue 4 (24th February 2017) - Peixoto, Maria Manuela; Nobre, Pedro
Abstract: Background: Despite the existence of conceptual models of sexual dysfunction based on cognitive theory, few studies have tested the role of vulnerability factors such as sexual beliefs as moderators of the activation of cognitive schemas in response to negative sexual events. Aim: To test the moderator role of dysfunctional sexual beliefs in the association between the frequency of negative sexual episodes and the activation of incompetence schemas in gay and heterosexual men. Methods: Five-hundred seventy-five men (287 gay, 288 heterosexual) who completed an online survey on cognitive-affective dimensions and sexual functioning were selected from a larger database. Hierarchical regression analyses were conducted to test the hypothesis that dysfunctional sexual beliefs moderate the association between the frequency of unsuccessful sexual episodes and the activation of incompetence schemas. Outcome: Participants completed the Sexual Dysfunctional Beliefs Questionnaire and the Questionnaire of Cognitive Schemas Activated in Sexual Context. Results: Findings indicated that men's ability for always being ready for sex, to satisfy the partner, and to maintain an erection until ending sexual activity constitute "macho" beliefs that moderate the activation of incompetence schemas when unsuccessful sexual events occur in gay and heterosexual men. In addition, activation of incompetence schemas in response to negative sexual events in gay men was moderated by the endorsement of conservative attitudes toward moderate sexuality. Clinical Implications: The main findings suggested that psychological interventions targeting dysfunctional sexual beliefs could help de-catastrophize the consequences of negative sexual events and facilitate sexual functioning. Strengths and Limitations: Despite being a web-based study, it represents the first attempt to test the moderator role of dysfunctional sexual beliefs in the association between the frequency of unsuccessful sexual episodes and the activation of incompetence schemas in gay and heterosexual men. Conclusion: Overall, findings support the role of sexual beliefs as facilitators of the activation of incompetence schemas in the face of negative sexual events in gay and heterosexual men, emphasizing the need to develop treatment and prevention strategies aimed at challenging common male beliefs about sexuality.